2020
DOI: 10.1021/acs.jcim.0c00947
|View full text |Cite
|
Sign up to set email alerts
|

Using Graph Databases to Investigate Trends in Structure–Activity Relationship Networks

Abstract: Mining the steadily increasing amount of chemical and biological data is a key challenge in drug discovery. Graph databases offer viable alternatives for capturing interrelationships between molecules and for generating novel insights for design. In a graph database, molecules and their properties are mapped to nodes, while relationships are described by edges. Here, we introduce a graph database for navigation in chemical space, analogue searching, and structure–activity relationship (SAR) analysis. We illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…For a similarity threshold of ϵ > 0.4 we compute an all-vs-all similarity metric using Tanimoto similarity, values less than ≤ 0.4 are set to zero to keep a sparse adjacency matrix (otherwise a computer runs into memory limitations). We take inspiration from [12, 21]. Compounds are encoded with a 4096 bit Morgan fingerprint in RDKit (Chirality=True, radius=3) and concatenated with the 166 bit MACCS key substructure fingerprint.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a similarity threshold of ϵ > 0.4 we compute an all-vs-all similarity metric using Tanimoto similarity, values less than ≤ 0.4 are set to zero to keep a sparse adjacency matrix (otherwise a computer runs into memory limitations). We take inspiration from [12, 21]. Compounds are encoded with a 4096 bit Morgan fingerprint in RDKit (Chirality=True, radius=3) and concatenated with the 166 bit MACCS key substructure fingerprint.…”
Section: Methodsmentioning
confidence: 99%
“…These network-based methods have found their way to established chemical bioinformatics companies (e.g. Chemaxon with Neo4j 1 ) and have been key tools for SAR campaigns [12]. Preliminary results on successfully utilising CSNs for lead-compound identification were recently demonstrated [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the traditional optimization rule summary, the MMP concept and method have also been applied in other aspects of drug design, such as scaffold hopping, graph database construction, focused library design, and especially de novo drug design. , Most importantly, MMPA can be applied to automatically design compounds with desired drug-like properties and biological activity. In 2019, Green et al reported BRADSHAW, an automated de novo design system that integrates chemical structure generation, experimental design, and active learning.…”
Section: Practical Applications Of Mmpamentioning
confidence: 99%
“…Chemical space networks (CSNs) have been developed to rationally engineer drugs by considering the chemical neighbourhood and building a structure-activity relationship (SAR) (4). However, these methods are difficult to scale due to the quadratic dependence on number of compounds and arbitrary design choices in their construction (5,6).…”
Section: Introductionmentioning
confidence: 99%